(untitled) (University of Khartoum Engineering Journal, 2023)
Soil stabilization otherwise known as soil modification or improvement, is the process of modifying soil properties to render them durable building and road construction materials by using various admixtures, the well-known being cement and lime. The aim of this study, however, to examine the stabilizing effect of banana extract on selected Sudanese lateritic soils. The objective of this study is to develop a new process for stabilizing lateritic soils. The three soil samples were blended with banana raw extract at 17% by weight of the dry soil at optimum extract content (soil + banana solution). High degree of improvement was obtained in both dry (12.60 – 30.54 N/mm²) and wet (1.03 – 5.03 N/mm²) compressive strength. It was concluded that, banana extract has a profound modifying effect over lateritic soils.